Seychelles : Staff Report for the 2019 Article IV Consultation and Third Review Under the Policy Coordination Instrument and Request for Modification of Targets and Monetary Consultation Clause-Press Release; Staff Report; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report ;, 2019)
Seychelles has made noticeable progress toward economic stability and sustainability under successive Fund programs through prudent macroeconomic policies and bold reforms since the crisis in 2008. Despite significant headway, the country remains vulnerable to external shocks as a small, open, and tourism-dependent economy. Seychelles could face challenges to reconcile its goals to reduce its infrastructure gap, enhance its resilience to climate change, and bolster its medium-term fiscal and external sustainability.